Loxosomella decorata n. sp., a new solitary entoproct from San Juan Island, WA, USA - Nielsen, Claus (Zootaxa, 2017)
Several species of solitary entoprocts of the genera Loxosoma and Loxosomella occur on maldanid polychaetes or in their tubes (Nielsen 1964). New species turn up almost every time maldanids from new localities are studied, and the species described below has been the subject of a study of spiral cleavage (Merkel et al. 2012). This paper describes a new species of Loxosomella from tubes of the maldanid polychaete Axiothella rubrocincta (Johnson, 1901) from False Bay, San Juan Island, WA, USA.